Влияние кластерного состава на границы действия диффузионных и конвективных механизмов в газовых смесях. Influence of cluster composition on the diffusion and convective mechanisms limit in gaseous mixtures - Молдабекова, М. С.; Косов, В. Н.; Федоренко, О. В. (Хабаршы. Физика сериясы, 2013)
Проведено исследование влияния кластерного состава в бинарных газовых смесях Ar–He и Ar-N2 на границу перехода «устойчивая диффузия – концентрационная гравитационная конвекция». Бинарные смеси аргон-гелий и аргон-азот рассматриваются как трехкомпонентные системы Ar-(Ar)2-Не и Ar-(Ar)2-N2. Кластерныйсостав тяжелого компонента Ar рассчитывался на основе анализа вириального уравнения состояния при различных температурах и давлениях. Система Ar–He исследовалась в диапазоне температур (301 – 353) К в цилиндрическом канале кругового сечения. Исследования по давлению в диапазоне (0.298 – 1.074) МПапроводились для системы Ar-N2 в плоском вертикальном канале. Полученные данные свидетельствуют о том, что при увеличении концентрации димеров Ar наблюдается рост критического числа Рэлея, определяющего переход из устойчивого состояния в неустойчивое.Study of the influence of cluster composition in binary gas mixtures Ar-He and Ar-N2 on the transition boundary between the stable diffusion and the concentration gravitation convection is carried out. Binary mixtures argonhelium and argon-nitrogen are considered as three-component systems Ar-(Ar)2-Не and Ar-(Ar)2-N2. Cluster composition of the heavy component Ar is calculated on the basis of virial state equation analysis at the different temperatures and pressures. System Ar-He is investigated in the temperature range (301.0 – 353.0) K in the circularcross-section cylindrical channel. Pressure researches in the range (0.298 – 1.074) MPa are conducted for the system Ar-N2 in the flat vertical channel. Finding indicates that the increase of critical Rayleigh numbers determining the transition from the stable state to the unstable one is observed with increasing dimmer concentration of Ar.